2016
DOI: 10.1016/j.imbio.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of C3-opsonin targeted complement inhibitors: A distinct advantage in the protection of erythrocytes from paroxysmal nocturnal hemoglobinuria patients

Abstract: Paroxysmal nocturnal hemoglobinuria (PNH) is characterized by complement-mediated cell lysis due to deficiency of GPI-anchored complement regulators. Blockage of the lytic pathway by eculizumab is the only available therapy for PNH patients and shows remarkable benefits, but regularly yields PNH erythrocytes opsonized with fragments of complement protein C3, rendering such erythrocytes prone to extravascular hemolysis. This effect is associated with insufficient responsiveness seen in a subgroup of PNH patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 60 publications
(84 reference statements)
2
41
0
Order By: Relevance
“…This is consistent with previous data showing that the C3-opsonintargeting inhibitors mini-FH and TT30 efficiently control AP activation in several assays. 38,44,45,49,50 As observed for the double inhibition of C5 in NHS (above), addition of coversin or PAS-coversin to the patientderived, eculizumab-containing serum completely stopped the residual hemolysis if compared with eculizumab alone. We verified that the patient sera indeed contained an excess amount of eculizumab over C5 ( Figure 1F).…”
Section: Single C5 Inhibition Only Partially Blocks Tp Activationmentioning
confidence: 77%
See 1 more Smart Citation
“…This is consistent with previous data showing that the C3-opsonintargeting inhibitors mini-FH and TT30 efficiently control AP activation in several assays. 38,44,45,49,50 As observed for the double inhibition of C5 in NHS (above), addition of coversin or PAS-coversin to the patientderived, eculizumab-containing serum completely stopped the residual hemolysis if compared with eculizumab alone. We verified that the patient sera indeed contained an excess amount of eculizumab over C5 ( Figure 1F).…”
Section: Single C5 Inhibition Only Partially Blocks Tp Activationmentioning
confidence: 77%
“…[42][43][44] Detailed descriptions are given in supplemental Methods, available on the Blood Web site.…”
Section: Proteinsmentioning
confidence: 99%
“…Initial PK and PD data demonstrate that TT30 treatment may result in pharmacologically relevant CAP inhibition in PNH, as supported by LDH decrease; nevertheless, further clinical development is hampered by the short half-life of this compound [174]. A different approach aiming to improve surface targeting of CFH exploits an engineered miniaturized version of CFH, named mini-FH; different versions of mini-FH have been described [175][176][177], all aiming to maximize the CAP inhibitory effect of CFH (C3 convertase decay and co-factor activities) at sites of complement activation [175]. Mini-FH (Amyndas, AMY-201) is a small (43 kDa) protein consisting of the regulatory complement control protein (CCP) 1-4 domains of CFH attached to its CCP 19-20 domains (which harbor a C3 binding-site) [175].…”
Section: Cfh-based Inhibitorsmentioning
confidence: 99%
“…This new class of surface-targeted inhibitors (e.g., AMY-201, Amyndas) has shown promising therapeutic results in an AP-driven disease model, protecting the erythrocytes of PNH patients from C3 opsonization and intravascular hemolysis (Schmidt et al , 2013). Notably, a recent study guided by molecular design has revealed distinct selectivity criteria that determine the relative inhibitory potency of surface-targeted C3 inhibitors on different C3-opsonized surfaces (Schmidt et al , 2016). In this context, mini-FH showed greater efficacy in abrogating complement activation on PNH erythrocytes, whereas other targeted regulator constructs showed distinct activities on different surfaces (Schmidt et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a recent study guided by molecular design has revealed distinct selectivity criteria that determine the relative inhibitory potency of surface-targeted C3 inhibitors on different C3-opsonized surfaces (Schmidt et al , 2016). In this context, mini-FH showed greater efficacy in abrogating complement activation on PNH erythrocytes, whereas other targeted regulator constructs showed distinct activities on different surfaces (Schmidt et al, 2016). These findings may better guide C3 therapeutic design by allowing us to tailor the application of surface-targeted inhibitors to appropriate pathologies.…”
Section: Introductionmentioning
confidence: 99%